Calcium regulation of muscle contraction. - Szent-Györgyi, A G (1975)
Calcium triggers contraction by reaction with regulatory proteins that in the absence of calcium prevent interaction of actin and myosin. Two different regulatory systems are found in different muscles. In actin-linked regulation troponin and tropomyosin regulate actin by blocking sites on actin required for complex formation with myosin; in myosin-linked regulation sites on myosin are blocked in the absence of calcium. The major features of actin control are as follows: there is a requirement for tropomyosin and for a troponin complex having three different subunits with different functions; the actin displays a cooperative behavior; and a movement of tropomyosin occurs controlled by the calcium binding on troponin. Myosin regulation is controlled by a regulatory subunit that can be dissociated in scallop myosin reversibly by removing divalent cations with EDTA. Myosin control can function with pure actin in the absence of tropomyosin. Calcium binding and regulation of molluscan myosins depend on the presence of regulatory light chains. It is proposed that the light chains function by sterically blocking myosin sites in the absence of calcium, and that the "off" state of myosin requires cooperation between the two myosin heads. Both myosin control and actin control are widely distributed in different organisms. Many invertebrates have muscles with both types of regulation. Actin control is absent in the muscles of molluscs and in several minor phyla that lack troponin. Myosin control is not found in striated vertebrate muscles and in the fast muscles of crustacean decapods, although regulatory light chains are present. While in vivo myosin control may not be excluded from vertebrate striated muscles, myosin control may be absent as a result of mutations of the myosin heavy chain.